The Nuclear Borderlands : The Manhattan Project in Post-Cold War New Mexico | New Edition - Masco, Joseph, 1964- (Book collections on Project MUSE., 2020)
"An important investigation of the sociocultural fallout of America's work on the atomic bomb"--